Involvement of Glutathione, Sulfhydryl Compounds, Nitric Oxide, Vasoactive Intestinal Peptide, and Heat-Shock Protein-70 in the Gastroprotective Mechanism of Croton cajucara Benth. (Euphorbiaceae) Essential Oil - Rozza, Ariane Leite [UNESP]; Moraes, Thiago de Mello [UNESP]; Kushima, Helio [UNESP]; Nunes, Domingos Savio; Hiruma-Lima, Clélia Akiko [UNESP]; Pellizzon, Claudia Helena [UNESP] (Mary Ann Liebert, Inc., 2011)
This study aimed to evaluate the gastroprotective mechanism of action of the essential oil of Croton cajucara Benth. (Euphorbiaceae) stem bark in ethanol-induced gastric ulcers and its in vitro anti-Helicobacter pylori activity. The involvement of heat-shock protein-70, vasoactive intestinal peptide, glutathione, nitric oxide, and nonprotein sulfhydryl compounds in the gastroprotective effect was determined in male Wistar rats. The minimum inhibitory concentration against H. pylori was determined in vitro. The results were analyzed by analysis of variance followed by the Dunnett test, and a P value less than 0.05 was considered to represent a statistically significant difference. C. cajucara decreased ethanol-induced ulcer area in 100% of ulcers and decreased the histologic lesions. In the C. cajucara group, the area marked by heat-shock protein-70 was significantly higher than the area in the control group; this finding was not seen for vasoactive intestinal peptide. C. cajucara could not maintain glutathione levels close to those in the sham group. The gastric ulcer area of rats treated with the sulfhydryl compound blocker was decreased, but the ulcer area of rats treated with nitric oxide synthase inhibitor showed no alteration. The minimum inhibitory concentration obtained for C. cajucara was 125 mu g/mL. These findings suggest that sulfhydryl compounds and heat-shock protein-70, but not nitric oxide, glutathione, or vasoactive intestinal peptide, are involved in the C. cajucara gastroprotective effect against ethanol-induced gastric ulcers.
Keywords: Croton cajucara; essential oil; gastroprotection; glutathione; heat-shock protein-70; medicinal plants; nitric oxide; sulfhydryl compounds